Gastrointestinal vasculitis due to systemic lupus erythematosus treated with rituximab: a case report. (May 2020) - Kenar, Gökçe; Atay, Kadri; Yüksek, Gül Emek; Öz, Burak; Koca, Süleyman Serdar
Background: Patients with systemic lupus erythematosus may present with variable gastrointestinal manifestations including peritonitis, pancreatitis, enteritis, and vasculitis. Gastrointestinal vasculitis is one of the most devastating complications of systemic lupus erythematosus, with a mortality rate of 50% when it progresses to bowel ischemia and is complicated by hemorrhage or perforation. Case report: A young female patient known to have systemic lupus erythematosus, lupus nephritis, and antiphospholipid antibody syndrome, on immunosuppressive treatment presented to the emergency department with acute abdominal pain and nausea. The clinical findings were first associated with an acute flare of lupus nephritis according to the assessments with active laboratory parameters. However, over a short time the abdominal pain worsened and was accompanied by peritonitis and gastrointestinal hemorrhage. The computed tomography scans demonstrated a dilated bowel and thickening of the bowel compatible with gastrointestinal vasculitis. The upper and lower gastrointestinal endoscopy supported the diagnosis of vasculitis by showing multiple ulcerative lesions along the gastrointestinal tract. The patient was successfully treated with pulse corticosteroids urgently, with a fast response to subsequent rituximab therapy without any relapses. Treatment with cyclophosphamide was not preferred because the patient had a high cumulative dose. Conclusion: Gastrointestinal vasculitis should be a primary differential diagnosis in patients with systemic lupus erythematosus presenting with abdominal pain because of its rapid progression and high mortality. The treatment choice has been suggested as cyclophosphamide for severe cases in the literature. In this case report, a patient successfully treated with rituximab without any relapses was documented.